Water and food to 2025: policy responses to the threat of scarcity - Rosegrant, Mark W.; Cai, Ximing; Cline, Sarah A. (International Food Policy Research Institute, 2002)
The world’s farmers will likely need to produce enough food to feed 8 billion people by 2025, and to do so they must have enough water to raise their crops. Yet farmers are already competing with industry, domestic water users, and the environment for access to the world’s finite supply of water. Will available freshwater meet the rapidly growing demands for household, industrial, and environmental needs and still provide enough water to produce food for a burgeoning population? New research from IFPRI shows what steps policymakers and water users can take now to help ensure that water scarcity will not result in worsening hunger for the world’s poorest people.